Retóricas híbridas em jornalismo impresso - (:unkn) unknown (Universidade Federal do Pampa, 2010)
The present theoretical study, of rhetorical-journalistic nature, about visual and verbal rhetorical hybridization in the printed journalism, was done in order to reach more scientific knowledge in the field of rhetorical hybridization. With this purpose, we collected and analyzed 20 editions of the “Folha de São Borja” newspaper, published from January to May in the currently year, 2010. In view of that, we carry out a bibliographic revision since the Classical Rhetorical, passing by the Aristotelic Rhetorical, and concluding with the New Rhetorical of Perelman (1999). With the intention of demonstrate the value of photo to the printed newspaper, we conducted a theoretical revision regarding the correlation between the photo and the writhed text, and the usefulness of visual and verbal rhetorical hybridization to the field of journalism. Based on the analyses, we conclude that the “Folha de São Borja” newspaper, usually, did not hybridize the visual and verbal rhetoric, once that there are no relationship between the writhed text and the photo that are accompanying it. Thus the persuasion could not be considered satisfactory. Finally, based on the performed analyses we realize the necessity of the theoretical knowledge to produce news in an efficient way.
Keywords: Jornalismo; Jornais; Retórica; Fotografia; Journalism; CNPQ::CIENCIAS SOCIAIS APLICADAS